KOORDINASI ANTARA PENYIDIK POLRES PADANG PARIAMAN DENGAN BADAN PERTANAHAN NASIONAL/ AGRARIA TATA RUANG KABUPATEN PADANG PARIAMAN DALAM PENYIDIKAN TINDAK PIDANA LARANGAN PEMAKAIAN TANAH TANPA IZIN - Rosadi, Otong; Hendra, Hendra (UNES Law Review, 2022)
Article 2 of Law Number 51 Prp of 1960 concerning Prohibition of Land Use Without Permission from the Entitled Person or his legal proxy. This research is a legal research with a descriptive analytical specification. The implementation of coordination between the Padang Pariaman Police Criminal Investigation Unit and the Padang Pariaman BPN/ATR in the investigation of the prohibition of land use without a permit or legal proxy is in terms of proving the status of ownership of the land. The National Land Agency was asked for information regarding land grabbing because the authorities and understanding of land grabbing are related to the legality of ownership of the land, even though the reporting party has shown proof of ownership but still requires information from the National Land Agency. Coordination is also carried out in terms of testing the validity of the documentary evidence collected by investigators in land grabbing cases. Obstacles in Coordination Between the Padang Pariaman Police Criminal Investigation Unit and Padang Pariaman BPN/ATR in Criminal Investigations for Prohibition of Land Use Without a Permit or Legal Proxy, among which are often difficult to distinguish the authenticity of proof of land ownership and the existence of overlapping land ownership which this cannot be proven by BPN as the institution that issued the evidence on the pretext of differences in leadership policies at that time. There are different agencies issuing proof of ownership of the same plot of land to different parties. The existence of falsification of land documents so that the Land Agency takes a long time to test the authenticity of these documents and makes the investigation take a long time.